Multi-cultural Switzerland – multicultural public service media? - Ratajczak, Magdalena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
In this article a special attention is paid to the to the role of public service broadcaster in cultural diversity societies. The main aims of the author was answering the following questions: how cultural pluralism is implemented by the public service broadcaster in Switzerland? How the Swiss PSB implements the principle of cultural pluralism, particularly in the context of the access of national, language communities and the migrants minorities to the media? Are all groups recognized by the public broadcaster in the same way? The second goal of the author was delivering answer to a question about the manner of how public broadcaster has adopted to the new situation and how the new ethnic groups are recognized by SGR SSR. The considerations are related to a cultural pluralism, which assumes that the media provide a guarantee of cultural diversity in a society. This article is a case study of Swiss public service broadcaster – SGR SSR idee suisse.

Artykuł zwraca szczególną uwagę na rolę nadawców publicznych w społeczeństwach wielokulturowych. Głównym celem była przede wszystkim odpowiedź na następujące pytania: w jaki sposób nadawca publiczny w Szwajcarii realizuje zasadę pluralizmu kulturowego, w jakim zakresie pluralizm kulturowy wpływa na prowadzenie polityki medialnej przez nadawcę publicznego oraz w jakim zakresie odmienne społeczności wyznaniowe, językowe, migranci mają dostęp do mediów publicznych w Szwajcarii? Czy wszystkie te grupy są w równym stopniu rozpoznawane przez nadawcę publicznego? Drugim istotnym celem tego artykułu jest analiza zmieniającej się sytuacji w Szwajcarii. Czy w związku z rosnącą liczbą nowych mniejszości zmienia się wobec nich polityka nadawcy publicznego? Artykuł stanowi studium przypadku szwajcarskiego nadawcy publicznego – SGR SSR idee suisse.
Wielokulturowa Szwajcaria – wielokulturowe media publiczne?
Keywords: Switzerland; multiculturalism; cultural diversity; public service broadcaster; Szwajcaria; wielokulturowość; różnorodność kulturowa; nadawca publiczny